Pre-service teacher education in competencies valued by the Primary teachers in active - Ángel De Juanas Oliva; Rosa Martín del Pozo (Revista Electrónica Interuniversitaria de Formación del Profesorado)
In this article we present the results of interviews with a sample of 48 teachers active in the Community of Madrid, previously surveyed on the preservice teacher education received in competencies they consider more fundamental and less, as well as those considered best and formed worse. These competitencies refer to: to involve families in learning of the children, educate in values, dominate the school content and to use ICT. Depending on the competence, it favors a particular mode of training and only for the domain of the school content is considered acceptable. It also discusses the changes proposed to improve preservice teacher education.